2013
DOI: 10.1111/1460-6984.12011
|View full text |Cite
|
Sign up to set email alerts
|

Disordered semantic activation in disorganized discourse in schizophrenia: a new pragma‐linguistic tool for structure and meaning reconstruction

Abstract: Latent sources, motivations and even meanings, at least to some extent, of seemingly disorganized utterances can become analysable through linguistic analyses. The results suggest that continuity in the treatment is essential, because a practitioner who shares background knowledge with the patient has better opportunities to capture the relevance of the superficially disorganized utterances. Moreover, especially the most disorganized sequences should warrant thorough attention because they can convey, beneath … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Andrews reported that the positive symptoms score of thought and attention disorder was negatively correlated with the average N400 amplitude in a time-window of 300–500 ms.[ 1 ] Until now, it is unclear if N400 reduction relates to real-world functioning and recovery. [ 14 15 ] This study found that the prolongation of N400 latency and decrease of N400 amplitude were negatively correlated with PANSS total score and positive symptoms score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrews reported that the positive symptoms score of thought and attention disorder was negatively correlated with the average N400 amplitude in a time-window of 300–500 ms.[ 1 ] Until now, it is unclear if N400 reduction relates to real-world functioning and recovery. [ 14 15 ] This study found that the prolongation of N400 latency and decrease of N400 amplitude were negatively correlated with PANSS total score and positive symptoms score.…”
Section: Discussionmentioning
confidence: 99%
“…The N400 component of event-related potentials (ERP) has recently drawn widespread attention at home and abroad. Its clinical value is that, not only is it most frequently used to assess diseases associated with linguistic disorder in the department of neurology and psychiatry,[ 1 2 ] but also, to effectively improve patients’ linguistic disorder has become an important candidate target of the research and development on the new generation of anti-psychotic drugs. [ 3 4 ] This research enrolled patients with first-episode schizophrenia (FES), who had never taken any antipsychotic drugs before, and carried out a 1-year follow-up on them.…”
Section: Introductionmentioning
confidence: 99%
“…Disorganized thinking in schizophrenia is associated with a reduction of fractional anisotropy in medial longitudinal fasciculus, which connects all the language regions, 19 justifying the alterations in the verbal fluency 20 and semantic in the hebephrenic patient. 21 This subtype also presents orbital, cingulated 22 and dorsolateral circuits dysfunction, 23 indicating a frontal multi-circuit deterioration, aiming a dark prognosis, even when psychotic symptoms have been controlled. 24 The subtypes of schizophrenia were recently eliminated by Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DMS-V), 14 due to the fact that almost all patients developed criteria for more than one subtype of schizophrenia during the illness course and generally are less used by psychiatrists.…”
Section: Introductionmentioning
confidence: 99%